Chemical Variations of Thermally Modified Wild-Grown Bambusa Vulgaris Schrad.Ex J.C. Wendl from Nigeria - O B, Olajide; O Y, Ogunsanwo; L O, Aguda; LT, Oriire (International Journal of Chemistry and Materials Research, 2022)
Determining the variation of chemical properties of thermally treated Bambusa vulgaris is important to provide the information of the responses of the chemical constituents to the bamboo modification against biodegradation. This research was therefore conducted to determine the chemical properties of thermally modified Bambusa vulgaris. Two hundred and seventy (30 x 2 x 0.5 cm) bamboo strips dimension were thermally modified in a heat-chamber at 100, 110, 120, 130 and 140 °C each, for 10, 20 and 30 minutes, under constant pressure (220 N/m2) in factorial arrangement in completely randomised design with 5 replicates. Unmodified strips served as control. Chemical characteristics (cellulose, hemicellulose, lignin and ash contents) were determined using standard procedures. The mean variation range of the control to 140°C/30 minutes of the thermally modified samples is as follows; the cellulose value ranged from 46.46±0.11% to 42.19±0.18%, hemicellulose from 35.59±0.10% to 31.80±0.01%, lignin from 29.11±0.12% to 26.17±0.13%, ash from 0.92±0.02% to 0.63±0.01%; the study also revealed that there were decrease in each chemical constituent value varies from a lower to a higher temperature and time regime proportionally except in the lignin content. Increase in temperature and time of thermal modification reduced the chemical characteristics of Bambusa vulgaris which resulted to reduction in the level of sugar contents (cellulose) of bamboo which enables it to be less attractive to both fungi and termite attack hence extending the service life of bamboo in use.